Peran STAIN Ponorogo dalam Memotivasi Sarjana Menjadi Wirausaha Muda Mandiri - Ika Susilowati (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
The role of a university in motivating its undergraduates to become young entrepreneurs is very important in growing the number of entrepreneurs. With the increase in entrepreneurs from among undergraduates, it will reduce the increase in unemployment and even increase the number of jobs. The question is how the college can produce young entrepreneurs. The role of higher education in fostering entrepreneurship can be explained by several opinions of experts in the field of entrepreneurship. One of them is explained by Thomas Zimmerer that one of the factors driving entrepreneurial growth is entrepreneurship education. In addition, Douglas A. Gray suggested starting a business early, for example when he was in college. While this study seeks to collect empirical data on motivational factors that encourage undergraduates to become entrepreneurs. The results of this study state that the satisfaction factor, the freedom to live life factor, and the opportunity factor, are factors that encourage STAIN Ponorogo alumni to decide to become entrepreneurs. So the role of universities, especially STAIN Ponorogo, is to provide information about opportunities, satisfaction and freedom to live what life will get if you become an entrepreneur, as well as provide entrepreneurship education, and provide a forum for students to apply their knowledge by setting up small businesses in locations around the college. The role of a university determines the creation of reliable young entrepreneurs.